Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 3

Answer

x = -3 y = 9

Work Step by Step

x + y = 6; y=-3x Substitute y for -3x to the first equation. x -3x = 6 -2x = 6 x = -3 (divide both sides by -2 ) Substitute x=-3 to the second equation. y = -3 $\times$ (-3) y = 9
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.